Identification of Novel STAT6-Regulated Proteins in Mouse B Cells by Comparative Transcriptome and Proteome Analysis - Mokada Gopal, Lavanya; Boeser, Alexander; Lehmann, Christian; Drepper, Friedel; Dudziak, Diana; Warscheid, Bettina; Vöhringer, David (Journal of Immunology, 2017)
The transcription factor STAT6 plays a key role in mediating signaling downstream of the receptors for IL-4 and IL-13. In B cells, STAT6 is required for class switch recombination to IgE and for germinal center formation during type 2 immune responses directed against allergens or helminths. In this study, we compared the transcriptomes and proteomes of primary mouse B cells from wild-type and STAT6-deficient mice cultured for 4 d in the presence or absence of IL-4. Microarray analysis revealed that 214 mRNAs were upregulated and 149 were downregulated >3-fold by IL-4 in a STAT6-dependent manner. Across all samples, 5000 proteins were identified by label-free quantitative liquid chromatography/mass spectrometry. A total of 149 proteins was found to be differentially expressed >3-fold between IL-4-stimulated wild-type and STAT6(-/-) B cells (75 upregulated and 74 downregulated). Comparative analysis of the proteome and transcriptome revealed that expression of these proteins was mainly regulated at the transcriptional level, which argues against a major role for posttranscriptional mechanisms that modulate the STAT6-dependent proteome. Nine proteins were selected for confirmation by flow cytometry or Western blot. We show that CD30, CD79b, SLP-76, DEC205, IL-5R?, STAT5, and Thy1 are induced by IL-4 in a STAT6-dependent manner. In contrast, Syk and Fc receptor-like 1 were downregulated. This dataset provides a framework for further functional analysis of newly identified IL-4-regulated proteins in B cells that may contribute to germinal center formation and IgE switching in type 2 immunity.
EVALuna2:25886